Permasalahan Penerapan Pendidikan Inklusi Di Sekolah Dasar - Abdul Hakim Hidayat; Anisa Rahmi; Nyai Ai Nurjanah; Yusuf Fendra; Wismanto Wismanto (Lembaga Pengembangan Kinerja Dosen, 2024)
Inclusive education is a critical issue in Indonesia, especially considering the high number of Children with Special Needs (CSN). Despite existing legal frameworks regulating inclusive education, its implementation remains limited, particularly at the Elementary School level. This study aims to explore the challenges faced in implementing inclusive education in Elementary Schools and evaluate the obstacles encountered by schools and teachers. The literature review method was employed to collect data through the analysis of various journals, books, and documents relevant to the research topic. The findings indicate numerous challenges in the implementation of inclusive education in Elementary Schools, including inadequate teacher competencies, lack of supporting facilities, insufficient tailored curricula, and the diverse characteristics of CSN requiring different approaches. Further efforts are needed to improve the inclusive education system in Indonesia to address these challenges.